Distribución de camarones inmaduros (Decapoda: Penaeidae) en el sistema lagunar de Alvarado, Veracruz, México - Sánchez, Alberto J (1993)
Immature Penaeus aztecus and P. setiferus shrimp are distributed throughout the lagoonal system of Alvarado. The first species dommates with respect 10 density (58%) and biomass (91 %). Both species are frequent in the seagrass beds along the inner margin of the bar of Alvarado, where they tend to concentrate. P. aztecus density increased with mean monthly salinities greater than 11% while the opposite occured in the case of P. setiferus. Shrimp densities are considered low compared to other estuarine systems of the Gulf of Mexico. Such low densities are related to hydro1ogical conditions and artisanal overfishing